Белковый состав ядерного матрикса в клетках различных тканей животных - Блохин, Д.Ю.; Стручков, В.А. (Биополимеры и клетка, 1989)
Белковый состав препаратов ядерного матрикса обладает выраженной видовой и тканевой специфичностью, выход суммарного белка в зтой фракции зависит от вида и пролиферативной активности клеток. В поддержании компактной структуры ядерного матрикса принимают участие дисульфидные группы белков. Білковому складу препаратів ядерного матриксу притаманна виражена видова і тканинна специфічність, вихід сумарного білка у цій фракції залежить від виду та проліферативної активності клітин. У підтримці компактної структури ядерного матриксу беруть участь дисульфідні групи білків. The protein composition of nuclear matrix preparations, isolated from different animal tissues under the same conditions, possesses species and tissue specificity. The preparations of nuclear matrix are resistant to additional treatments with dissociating agents (EDTA, NaCl, urea), but their incubation in the presence of thiols results in dissociation of some proteins, that confirms the assumption on participation of disulfide intersubunit bonds in organization of skeletal structures of interphase nucleus.